2019
DOI: 10.1007/s00345-019-02810-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ureteroscopy for stone disease in anomalous kidneys: a systematic review

Abstract: Introduction Treatment of stone disease in anomalous kidneys can be challenging. As ureteroscopy (URS) has advanced, the number of studies reporting on outcomes of URS for stone disease in anomalous kidneys has increased. Our objective was to perform a systematic review of the literature to evaluate the outcomes of URS for stone disease in this group of patients. Methods A Cochrane style review was performed in accordance with the PRISMA guidelines using Medline, EMBASE, CINAHL, Cochrane Library, Scopus and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Anomalous kidneys arise from different abnormalities in the embryological development: abnormal ascent, fusion, rotation, or a combination of these. Anatomical anomalies not only lead to compromised renal drainage, but also increase the risk of urolithiasis [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anomalous kidneys arise from different abnormalities in the embryological development: abnormal ascent, fusion, rotation, or a combination of these. Anatomical anomalies not only lead to compromised renal drainage, but also increase the risk of urolithiasis [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have evaluated the safety profile and success rates of the procedure in abnormal kidneys, and the findings consistently demonstrate low complication rates. However, the stone-free rate did not exceed 90% in nearly all cases [ 32 , 65 - 67 ]. A 2017 study by Ergin et al [ 68 ] assessed success rates (stone-free) in 101 patients with renal lithiasis and associated renal anatomical anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Although ureteroscopy may be difficult in these particular patients, a systematic review conducted in 2020 by Lisa Lavan et al [ 32 ] examined 117 cases of ectopic kidney along with other kidney anomalies and demonstrated that endourological technique advancements had made ureteroscopy an effective and safe procedure, combined with minimal rates of complications and promising postoperative stone-free status. A study conducted by Omer Faruk Bozkurt et al [ 33 ] investigated retrograde fURS management in 26 patients with renal lithiasis associated with ectopic kidneys [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, not only no complications were observed, but also the efficacy of FURS was similar to PNCL. Lavan et al ( 27 ) published a more recent review on the outcomes of ureteroscopy for stone disease in anomalous kidneys, and they reported that patients who underwent FURS got good stone-free rates with a low risk of major complications, although the technic is challenging. This evidence indicated that SWL and FURS could be a feasible and safe alternative in patients with HK with calculus.…”
Section: Discussionmentioning
confidence: 99%